2021
DOI: 10.31605/jepa.v4i1.1219
|View full text |Cite
|
Sign up to set email alerts
|

Motivasi Belajar Terhadap Hasil Belajar Mahasiswa Pada Pembelajaran Daring Saat Pandemi Covid-19

Abstract: ABSTRAK Tujuan riset ini adalah untuk mengetahui pengaruh pembelajaran daring dan motivasi belajar terhadap hasil belajar mahasiswa pada masa pandemi Covid-19. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei menggunakan skala Likert dengan melakukan  penyebaran kuesioner yang dibuat dalam bentuk google form. Teknik pengambilan sampel menggunakan random sampling yaitu mahasiswa yang mengambil mata kuliah kompetensi semester VI program studi manajemen yang berjumlah 75 mahasiswa. Tek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
1
1
0
6
Order By: Relevance
“…This researcher was strengthened by the results of previous research which stated that discipline has a positive relationship with motivation, the data shows a high level of reliable interpretation, and the magnitude of the influence of learning motivation on science learning achievement is 48.1 (Simba et al, 2016). Other findings from research results confirm that motivation has a large effect on student learning outcomes (Asmawiyah, 2021). The results of this study were also supported by the results of research which showed that there was a positive and significant relationship between learning discipline and learning motivation with PKN learning outcomes for fifth-grade students (Isnaeni & Sumilah, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This researcher was strengthened by the results of previous research which stated that discipline has a positive relationship with motivation, the data shows a high level of reliable interpretation, and the magnitude of the influence of learning motivation on science learning achievement is 48.1 (Simba et al, 2016). Other findings from research results confirm that motivation has a large effect on student learning outcomes (Asmawiyah, 2021). The results of this study were also supported by the results of research which showed that there was a positive and significant relationship between learning discipline and learning motivation with PKN learning outcomes for fifth-grade students (Isnaeni & Sumilah, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…This shows that discipline and learning motivation greatly influence learning outcomes because discipline and learning motivation can encourage students to participate in learning activities properly. The higher the discipline and learning motivation of students, the better the learning outcomes of students (Asmawiyah, 2021;Mardiani, 2021). Discipline and learning motivation of students cannot be built by themselves, because student discipline can be realized based on awareness within each student.…”
Section: Discussionmentioning
confidence: 99%
“…Temuan dari penelitian berseberangan dengan (Novalinda et al, 2018) yang menegaskan bahwa motivasi berpengaruh besar akan hasil belajar siswa. Bersama dengan itu, temuan penelitian ini menentang penelitian (Asmawiyah, 2021) yang menunjukkan bahwa motivasi meningkatkan hasil belajar siswa. Sedangkan (Ramadhan, 2015) mendukung temuan penelitian ini dengan menyatakan bahwa motivasi tidak memiliki pengaruh yagng nyata terhadap hasil belajar untuk pelajaran ekonomi kelas X SMAN 2 Sungai Ambawang.…”
Section: Pengaruh Motivasi Terhadap Hasil Belajar Siswaunclassified
“…Pembelajaran daring merupakan sebuah sistem yang diaplikasikan pada dunia pendidikan dengan proses belajar mengajar jarak jauh dengan metode pengajaran diterapkan melalui jaringan internet (Asmawiyah et al, 2021). Pembelajaran daring dapat membantu mempermudah sebagai sarana akses belajar mengajar yang dapat memberikan manfaat bagi mahasiswa dan proses pembelajaran dapat dilakukan dimanapun dan kapanpun (Juliya & Herlambang, 2021).…”
Section: Pendahuluanunclassified
“…Hasil belajar merupakan tolak ukur pencapaian pada proses pembelajaran yang dilakukan oleh tenaga pengajar dan mahasiswa. Penelitian yang dilakukan oleh (Asmawiyah et al, 2021) pembelajarn secara daring di masa pandemi dikarenakan kurangnya sarana prasarana dan selain itu juga tidak terdapatnya motivasi belajar yang dimiliki oleh para mahasiswa yang memiliki dampak juga pengaruh terhadap hasil pembelajaran tersebut (Ferazona & Suryanti, 2020).…”
Section: Pendahuluanunclassified